Constructive feminism : women's spaces and women's rights in the American city - Spain, Daphne (Cornell University Press, 2016)
This book examines the deliberate and unintended spatial consequences of feminism's second wave, a social movement dedicated to reconfiguring power relations between women and men. Placing the women's movement of the 1970s in the context of other social movements that have changed the use of urban space, this book argues that reform feminists used the legal system to end the mandatory segregation of women and men in public institutions, while radical activists created small-scale places that gave women the confidence to claim their rights to the public sphere.